2006
DOI: 10.1111/j.1365-2885.2006.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450‐dependent metabolism of midazolam in hepatic microsomes from chickens, turkeys, pheasant and bobwhite quail

Abstract: In vitro putative cytochrome P450 3A mediated activity, and inhibition thereof, were measured in four avian species using midazolam (MDZ) as a substrate and ketoconazole as an inhibitor. All species produced 1-hydroxymidazolam (1-OH MDZ) to a much greater extent than 4-hydroxymidazolam (4-OH MDZ). Calculated Vmaxapparent values for formation of 1-OH MDZ were 117+/-17, 239+/-108, 437+/-168, and 201+/-55 pmol/mg protein*min and Kmapparent values were 2.1+/-0.8, 2.4+/-1.6, 6.7+/-5.1 and 3.2+/-2.1 microm for chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…When comparing the ratio of the two metabolites produced in each species in the current study with those obtained from in vitro studies (Cortright & Craigmill, 2006), the ratios of 1‐OH MDZ to 4‐OH MDZ were identical for chicken and almost identical for turkey. However, pheasant and bobwhite quail, while still producing 1‐OH MDZ as the major metabolite, did produce a higher ratio of 4‐OH MDZ relative to 1‐OH MDZ in vivo than was seen in vitro , especially at the later time‐points.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…When comparing the ratio of the two metabolites produced in each species in the current study with those obtained from in vitro studies (Cortright & Craigmill, 2006), the ratios of 1‐OH MDZ to 4‐OH MDZ were identical for chicken and almost identical for turkey. However, pheasant and bobwhite quail, while still producing 1‐OH MDZ as the major metabolite, did produce a higher ratio of 4‐OH MDZ relative to 1‐OH MDZ in vivo than was seen in vitro , especially at the later time‐points.…”
Section: Discussionmentioning
confidence: 65%
“…Previous in vitro studies of MDZ metabolism in hepatic microsomes in these species found that the V max , the apparent maximal enzyme velocity, for formation of 1‐OH MDZ, from highest to lowest, was pheasant, turkey, bobwhite quail, and chicken (Cortright & Craigmill, 2006). However, the corresponding Michaelis‐Menten constant value, the K m or substrate concentration at which the enzyme is operating at half‐maximal velocity, from highest to lowest, were pheasant, bobwhite quail, turkey and chicken.…”
Section: Discussionmentioning
confidence: 96%
“…An attempt was made to use the Michaelis–Menton parameters for hepatic metabolism estimated from an earlier in vitro study (Cortright & Craigmill, 2006). However, the current study did not show zero order kinetics and to fit the experimental data the model V max value had to be increased so much as to approximate linear clearance.…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially useful for predicting residues in so-called 'minor' species (fish, goats, sheep, pheasant and quail) where therapeutic drugs have been tested and approved for use in 'major' economic species, but not for minor species that are susceptible to the same diseases. Previous work by our laboratory has focused on comparative in vitro and in vivo drug studies to see if minor species pharmacokinetics ⁄ tissue residues can be modelled using empirical data from major species (Cortright & Craigmill, 2006;Cortright et al, 2007).The aim of the current paper is to describe the development and optimization of a PBPK model in chickens for the pharmacokinetics and tissue residues of midazolam after intravenous (i.v.) administration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MDZ has already been used in different avian species as a substrate for CYP3A (Cortright & Craigmill, ). In chickens, the production of MDZ metabolites in liver microsomes demonstrated Michaelis–Menten kinetics with K m equal to 2.1 ± 0.8 μ m for 1‐OH‐MDZ (Cortright & Craigmill, ). Therefore, MDZ was also used in our study to evaluate the CYP3A activity in liver and intestines of the broilers.…”
Section: Discussionmentioning
confidence: 99%